Variables Associated with Chondral and Meniscal Injuries in Anterior Cruciate Ligament Surgery - Cain, E. Lyle, Jr.; Fleisig, Glenn S.; Ponce, Brent A.; Boohaker, Hikel A.; George, Martha P.; McGwin, Gerald, Jr.; Andrews, James R.; Lemak, Lawrence J.; Clancy, William G., Jr.; Dugas, Jeffrey R. (The Journal of Knee Surgery, 2017)
This article aims to evaluate factors associated with chondral and meniscal lesions in primary and revision anterior cruciate ligament (ACL) reconstructions. ACL reconstructions from 2001 to 2008 at a single institution were retrospectively analyzed. Logistic regression was used to estimate the association between chondral and meniscal injuries and age, gender, tear chronicity, additional ligamentous injuries, sport type, and participation level. Of the 3,040 ACL reconstructions analyzed, 90.4% were primary reconstructions and 9.6% were revisions. Meniscal injuries were significantly lower in the revision group (44.0 vs. 51.9%; p = 0.01), while chondral injuries were significantly higher in the revision group (39.9 vs. 24.0%; p < 0.0001). Inspection of the small subgroup (n = 85) receiving both primary and revision ACL surgery at our center indicated that meniscal injuries at revision were evenly split between menisci with and without previous repairs, whereas the vast majority of Grade III and IV chondral lesions were new. More patients presented for surgery later in the revision group than in the primary group (56.5 vs. 35.3%; p < 0.0001). Male gender, primary reconstruction, and short interval (less than 2 weeks) between injury and surgery were associated with increased likelihood of meniscus tear. Age (greater than 22 years) and long interval (greater than 6 weeks) between injury to surgery and higher sport activity level were associated with chondral lesions. Revision ACL reconstructions are associated with a higher proportion of chondral lesions and a lower proportion of meniscal tears. Early primary and revision ACL construction is recommended to reduce the probability of chondral lesions.
Keywords: ACL reconstruction; ACL revision; meniscus; chondral lesion; cartilage